2009
DOI: 10.1002/prot.22427
|View full text |Cite
|
Sign up to set email alerts
|

Native secondary structure topology has near minimum contact energy among all possible geometrically constrained topologies

Abstract: Secondary structure topology in this article refers to the order and the direction of the secondary structures, such as helices and strands, with respect to the protein sequence. Even when the locations of the secondary structure Calpha atoms are known, there are still (N!2(N))(M!2(M)) different possible topologies for a protein with N helices and M strands. This work explored the question if the native topology is likely to be identified among a large set of all possible geometrically constrained topologies t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…Although there are different topologies, the ones that satisfy the density requirement and the -sheet constraints can be quite limited. The results in this paper further demonstrated our previous finding about the amazing properties of SSE topologies that is the native topology is near the top of the entire topological space [31]. Figure 5 shows an example of the correct and incorrect topology.…”
Section: Test With β-Sheetssupporting
confidence: 86%
“…Although there are different topologies, the ones that satisfy the density requirement and the -sheet constraints can be quite limited. The results in this paper further demonstrated our previous finding about the amazing properties of SSE topologies that is the native topology is near the top of the entire topological space [31]. Figure 5 shows an example of the correct and incorrect topology.…”
Section: Test With β-Sheetssupporting
confidence: 86%
“…Given the positions of a helices and b strands in a density map, one can match them with secondary structure sequence segments that can be predicted from the amino acid sequence to derive the overall topology of a protein chain (Al Nasr et al, 2011;Baker et al, 2011;Biswas et al, 2012;Lindert et al, 2012;Lu et al, 2008). Once the topology is determined, backbone and side chains can be constructed and evaluated using energy functions (Al Nasr et al, 2010;Lindert et al, 2012;Sun and He, 2009). Pathwalking derives a Ca trace directly from pseudoatoms extracted from the density map (Baker et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that DP-TOSS, a constrained K-shortest path method, is effective finding the topology from large proteins such as those with 33 helices [14]. Once limited possible matches are predicted, atomic models can be built and selected using energy functions [15][16][17][18]. Although it is possible to detect the location of major β-sheets, it has been a challenging problem to detect β-strands from the β-sheet density.…”
Section: Introductionmentioning
confidence: 98%